EFFECTS OF MYCORRHIZAL INOCULATION ON GROWTH, NITROGEN AND PHOSPHORUS CONTENTS OF TWO TROPICAL FORAGE LEGUMES - Paulino, V. T.; Costa, N. L.; Schammas, E. A. (REVISTA DE AGRICULTURA, 2020)
EFFECTS OF MYCORRHIZAL INOCULATION ON GROWTH, NITROGEN AND PHOSPHORUS CONTENTS OF TWO TROPICAL FORAGE LEGUMES